2014
DOI: 10.1902/jop.2014.140230
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Activator of Nuclear Factor‐κB Ligand and Sclerostin Expression in Osteocytes of Alveolar Bone in Rats With Ligature‐Induced Periodontitis

Abstract: These results show that AB loss is accompanied by enhanced osteoclast formation and suppressed osteoid formation. Osteocytes express RANKL when osteoclast formation increases, and they express sclerostin when osteoid formation is suppressed. Conversely, osteocytic sclerostin expression decreases when osteoid formation increases. These findings suggest that osteocytes may be important in AB loss via RANKL and sclerostin expression in periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 40 publications
(91 reference statements)
6
33
0
1
Order By: Relevance
“…In this study, ABL similarly increased at day 3 after ligature placement in the P and DP groups. Consistent with the authors’ previous study, 10 ABL in the P group did not further increase at day 20 after ligature placement. However, the ABL observed in the DP group increased more than that observed in the P group at day 20, and the increase was continual from ligature to day 20.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, ABL similarly increased at day 3 after ligature placement in the P and DP groups. Consistent with the authors’ previous study, 10 ABL in the P group did not further increase at day 20 after ligature placement. However, the ABL observed in the DP group increased more than that observed in the P group at day 20, and the increase was continual from ligature to day 20.…”
Section: Discussionsupporting
confidence: 92%
“…At day 3 after ligature placement, when osteoid formation markedly decreased in both groups, sclerostin expression increased. At day 20 after ligature placement, when osteoid formation in the P group notably increased, sclerostin expression decreased, which was also observed in the authors’ previous study 10 . Interestingly, increased sclerostin expression in the DP group was sustained until day 20 after ligature placement, at which time diminished bone formation was also observed.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A study on ligature‐induced periodontitis in rats demonstrated an increased expression of osteocytic SOST, which correlated with suppressed osteoid formation. Increased amounts of RANKL expression was also correlated with the accumulation of osteoclasts . In addition to its anti‐anabolic effects, SOST also acts through the Wnt/β‐catenin pathway and increases RANKL, resulting in bone resorption.…”
Section: Discussionmentioning
confidence: 94%
“…In pathological conditions, sclerostin expression is altered in response to inflammatory molecules such as TNFα. Recently, a study using a rat model of ligature‐induced periodontitis revealed significant increases in sclerostin expression in osteocytes during the early and destructive phase of the disease . Interestingly, the rise in sclerostin levels was associated with a similar increase in RANKL production.…”
Section: Effects Of Tumour Necrosis Factor‐α On Osteocytes and Their mentioning
confidence: 99%